Pengaruh Kualitas Produk, Brand Image, dan Promosi Terhadap Keputusan Pembelian Air Kemasan Merek AQUA di Tengah Isu Negatif : (Studi Kasus Pada Mahasiswa Prodi Manajemen Angkatan 2021 Universitas Bhayangkara Jakarta Raya) - Arzety, Adelia Vita; Kurniawan, Dody; Husadha, Cahyadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the influence of the independent variables Product Quality, Brand Image, and Promotion on the dependent variable Purchase Decision, both simultaneously and partially. The research method used is a quantitative approach with purposive sampling technique, calculated using the Slovin formula. The population in this study consists of Management students from the 2021 class at Universitas Bhayangkara Jakarta Raya, with a sample size of 96 respondents. Based on the results of the partial test (t-test), the Product Quality variable has a positive and significant effect on Purchase Decision, with a t-value of 4.353 > t-table 1.986 and a significance value of 0.000 < 0.05. The Brand Image variable also has a positive and significant partial effect on Purchase Decision, with a t-value of 5.079 > t-table 1.986 and a significance value of 0.000 < 0.05. Similarly, the Promotion variable shows a positive and significant effect on Purchase Decision, with a t-value of 5.203 > t-table 1.986 and a significance value of 0.000 < 0.05. Furthermore, the simultaneous test (F-test) shows that the three independent variables Product Quality (X1), Brand Image (X2), and Promotion (X3) together have a positive and significant effect on Purchase Decision (Y), with an F-value of 74.041 > F-table 2.70 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) result indicates that the three independent variables explain 69.8% of the variation in the dependent variable.